Seeing through the farmers’ eyes: An exploration of the life of smallholder farmers in Northern Uganda - Acosta, Mariola; Riley, Simon; Giller, Onno; Jassogne, Laurence T.P. (International Institute of Tropical Agriculture, 2018)
All too often, the well-intentioned efforts of journalists and development organizations to raise awareness of pressing humanitarian issues has the unintended effect of reducing its human subjects to little more than hapless victims of the latest calamity. Ugandans are hardly alone in having a portrait - spread through images on television and social media across both the Global North and South - which reflects little other than their suffering and privation: the mothers of children with swollen bellies carry home heavy jerry cans of water from far-off wells while their fathers watch helplessly as the crops wither in the field. While food insecurity and the challenges of coping with a changing climate are, tragically, a very real part of many rural Ugandans daily lives, they are neither the whole of those lives nor are they necessarily perceived and understood in the way an outsider might.